STRUCTURAL REFINEMENT OF SAMARIUM BISMUTH TITANATE USING RIETVELD METHOD - Al-Amani, Umar (2009)
The crystal structure of Bismuth titanate (BT) and Samarium Bismuth titanate (SBT) was analyzed using Rietveld method. Through the analysis, we found that the orthorhombic structure of BT was gradually changed to be a tetragonal structure which belongs to the SBT' A great influence was clearly seen on the crystal structure as a result of Samarium content added to the system. Other parameters such as lattice parameter, volume unit and crystallite size were also changed due to such addition.